THE EFFECTIVENESS OF RUPBASAN ON STATE CONFISCATED PROPERTY CASE STUDY OF CLASS 1 CIREBON RUPBASAN - Ardiansyah Ardiansyah; Aprilia Maulani; Umair Umair; Tazqia Anandhita; Ade Jahasan (Jurnal Abdisci, 2025)
Abstract Background. Indonesia guarantees the ownership of goods in the 1945 constitution, as stated in Article 28 H paragraph (4), which states that "Everyone has personal property rights and such property rights may not be arbitrarily taken over by anyone, " but only if the goods are obtained illegally. Therefore, the state has the right to carry out coercive efforts against citizens if they are strongly suspected of committing unlawful acts. Law enforcement officials can confiscate goods suspected to be the result of criminal acts for the purpose of proof at the level of investigation, prosecution, and trial, including goods confiscated as an implementation of a judge's decision that has permanent legal force. Aims.Based on Law No. 8 of 1981 concerning the Criminal Procedure Code (KUHAP) article 44 paragraph (1) State confiscated objects are stored in the State Confiscated Objects Storage House. However, in the storage of state confiscated goods, Rupbasan has a number of challenges, namely how effective is the authority to regulate the storage of state confiscated goods by Rupbasan? and what factors affect the performance of Rupbasan? Methods. This writing uses doctrinal-empirical methods presented with analytical descriptiveness. The data collection carried out in this writing is a literature study and interviews. Result. The paper will examine the effectiveness of Rupbasan's role in storing confiscated goods, the challenges faced by Rupbasan in regulating the authority of other agencies/institutions to store state confiscated goods that can shift the role of Rupbasan itself, and factors that hinder Rupbasan's performance in storing state confiscated goods.